Venezuelan Government Disclaimer toward Humanitarian Assistance of International Communities - Kumajaya, Kumajaya; Setiawan, Rachmat (Universitas Muhammadiyah Yogyakarta, 2019)
This paper discusses the factors that became the reason for Venezuela in rejecting humanitarian assistance from the international community for the humanitarian tragedy occurring in the country. This study employed a constructivist approach in looking at the relationship between sense of identity and sense of vulnerability in analyzing the Venezuelan response to the entry of international humanitarian aid from United Nations (UN) agencies into the country. The results revealed that the rejection of international community assistance by the Venezuelan government aimed to protect the country from intervening interests of international actors.